Precipitation characteristics and trend in the Hsiao-Ching river basin of Jinan city during the past 50 years - Lin, L.; Liu, Jian; Huang, J.; Chen, X.; Guan, Q.; Tang, Y. (2014)
Monthly precipitation data from Huangtai Bridge Station were used to study seasonal and annual precipitation characteristics and trend. The covered time-period is from 1956 to 2007. Different methods including linear regression, 5-year moving average, anomalies in decadal scale and the Mann-Kendall test were applied in the study. Nearly two-thirds of the total rainfall amount is concentrated in summer, with autumn and spring months to follow, and only about 3% in winter. An increasing trend in spring months is found. It starts in 1978, becomes significant after 2002, and probably continues into the future. A decreasing trend is recorded in winter and begins in 1980. No significant trend is found in summer, autumn and yearly precipitation. The same fluctuations are observed between summer and annual precipitation indicating the dominant influence of the summer season.